Implementasi Clinical Pathway Kasus Tuberkulosis Paru Berdasarkan Rekam Medis Pasien di RSUD dr. Soekardjo Kota Tasikmalya - Namira Fatimah Azahra; sugiarti, Ida (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Hospitals should have tools to control the quality of services provided to patients so that health services provided by health workers can be integrated and can reduce risks in the process of clinical services. One tool to control the quality of service is a clinical pathway. Preparation of clinical pathways at Dr. Soekardjo, Tasikmalaya City, based on five criteria in filling out the clinical pathways for pulmonary tuberculosis cases in this study included initial examination, follow-up examination, management, evaluation, and validation. Implementation of a clinical pathway for pulmonary tuberculosis cases based on patient medical records in the third quarter of 2022 at Dr.Soekardjo Hospital Tasikmalaya City. This type of research is a quantitative method, the implementation of clinical pathways at Dr. Soekardjo Hospital has been carried out well with the results obtained for the initial review examination carried out as many as 63 files (76%), the average follow-up review examination was carried out as many as 77 files (93 %), the average management review is 74 files (89%), the average evaluation review is 79 files (95%), the average authentication review is 83 files (100%).